Recent advances in the influences of drying technologies on physicochemical properties and biological activities of plant polysaccharides - Guo, Huan; Liu, Hong-Yan; Li, Hang; Wu, Ding-Tao; Zhong, Linda L. D.; Gan, Ren-You; Gao, Hong (Critical reviews in food science and nutrition, 2024)
Plant polysaccharides, as significant functional macromolecules with diverse biological properties, are currently receiving increasing attention. Drying technologies play a pivotal role in the research, development, and application of various foods and plant polysaccharides. The chemical composition, structure, and function of extracted polysaccharides are significantly influenced by different drying technologies (e.g., microwave, infrared, and radio frequency) and conditions (e.g., temperature). This study discusses and compares the principles, advantages, disadvantages, and effects of different drying processes on the chemical composition as well as structural and biological properties of plant polysaccharides. In most plant-based raw materials, molecular degradation, molecular aggregation phenomena along with intermolecular interactions occurring within cell wall components and cell contents during drying represent primary mechanisms leading to variations in chemical composition and structures of polysaccharides. These differences further impact their biological properties. The biological properties of polysaccharides are determined by a combination of multiple relevant factors rather than a single factor alone. This review not only provides insights into selecting appropriate drying processes to obtaining highly bioactive plant polysaccharides but also offers a fundamental theoretical basis for the structure-function relationship of these compounds.